2023
DOI: 10.3390/electronics12112497
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality Enabled Interventions for Autism Spectrum Disorder: A Systematic Review and Meta-Analysis

Abstract: Autism spectrum disorder (ASD) is characterized by persistent deficits in social communication and interaction, which can have significant impacts on daily life, education, and work. Limited performance in learning and working, as well as exclusion from social activities, are common challenges faced by individuals with ASD. Virtual reality (VR) technology has emerged as a promising medium for delivering interventions for ASD. To address five major research questions and understand the latest trends and challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…Therefore, when designing VR systems and implementing instruction, the theoretical basis is very important, but in the process of coding, only six articles mentioned frameworks, models, concepts, and theories. This finding aligns with those reported by Li and Belter [37].…”
Section: Instructional Designsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, when designing VR systems and implementing instruction, the theoretical basis is very important, but in the process of coding, only six articles mentioned frameworks, models, concepts, and theories. This finding aligns with those reported by Li and Belter [37].…”
Section: Instructional Designsupporting
confidence: 94%
“…Out of all of the studies, 44% included participant populations that were mostly male (male participants made up more than two-thirds of the total, n = 14), 34% had a gender balance (n = 11), and 9% were all male (n = 3). This is similar to the findings of Li et al [37] and Mesa-Gresa and Gil-Gómez [32], where the study populations tended to include more male participants. Furthermore, only half of the studies reported grade levels, two were of preschool age, nine were for primary school children, two were for secondary school students, and three were for both primary and secondary school students.…”
Section: Participant Characteristicssupporting
confidence: 90%
“…In addition to the Evidence Based Practice above, recent studies have shown that virtual reality (VR) technology can be a promising medium for providing ASD interventions. (Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some virtual reality (VR) contents have been used for individuals with autism-spectrum disorder (ASD) or higher autistic individuals (Lorenzo et al, 2013;Ip et al, 2018;Kumazaki et al, 2021;Li et al, 2023). ASD is a developmental disorder characterized by difficulties in social interactions and excessively limited behavioral patterns and interests (American Psychiatric Association, 2013).…”
Section: Introduction 1immersive Visual Guidance Technique Assists Us...mentioning
confidence: 99%